Female genital mutilation (FGM) in Somaliland – why is change so slow? - Johansson, Annika; Osman Gaas, Abdirahman; Mahmoud Warsame, Amina (Somali Health Action Journal, 2021)
Female genital mutilation (FGM) is defined as any procedure involving the alteration or excision of external female genitalia for no medical reason. Somaliland has among the highest prevalence rates of FGM globally. In this article we describe how the Civil Society Organisation (CSO) ‘Network against female genital mutilation in Somaliland’ (NAFIS) has approached the challenge to reduce the high FGM prevalence. From its start in 2006, NAFIS has developed a multifaceted program to reach the overall goal: the elimination of all forms of FGM in Somaliland. Alone among the group of CSOs in the network, NAFIS introduced in its activities medical care and counselling for women who suffer from the consequences of FGM. From 2011 and onwards, thousands of women have been relieved of their FGM-related health complications and participated in counselling sessions at project centres. Shortly after this visit they have been invited to participate in community group meetings to share their experiences with other women who also have received FGM care and counselling, and other community members. The aim of the article is to describe this model of work - combining FGM care and counselling with community dialogues. The article is basically descriptive, using the authors’ own observations and encounters with project clients and staff over eight years. We have also used findings from three Master's theses on aspects of the process, and from other small scale studies to highlight people’s understanding, experiences and opinions in a context of an on-going health intervention. A lesson learnt from NAFIS project is that it has helped to open up communicative spaces in community dialogues where experiences are shared and understanding created of the harm caused by FGM, without the habitual stigma and shame. We discuss this process in a context of behavioural change theories. A major challenge during the process has been to involve men in the project’s FGM information and counselling activities. The role of nurses/midwives, being the first to meet women with FGM complications, is also discussed and the need emphasised to strengthen capacity of this category of health workers. One type of FGM gaining in usage is the poorly defined sunna, the health risks of which are unclear.